Understanding Customer Satisfaction: Evaluating Product Quality And Marketing Mix of Koffee Talk At Radja Hotel Semarang - Ricky Anggrean; Enik Rahayu; Hendrajaya, Hendrajaya; Heni Krisnatalia; Bayu Ade Prabowo (PT. Banjarese Pacific Indonesia, 2024)
The research was carried out at Koffee Talk, which is located inside the Radja Hotel Semarang. The purpose of the study was to evaluate and explain the influence that the quality of service and marketing mix had on the level of satisfaction experienced by customers. Questions and answers are gathered via the use of questionnaires. Participants in the research totaled 96 individuals. It is anticipated that the findings of the study would be beneficial to both management and customers. Customer happiness is impacted by both the quality of the service and the marketing mix. The findings of the double regression analysis demonstrate the impact of independent factors on dependent variables, as well as the validity and rehabilitation tests, as well as the testing of hypotheses. It is clear that in order to achieve higher levels of customer satisfaction, a combination of marketing and service is required.